George Moore and the autogenous self : the autobiography and fiction - Grubgeld, Elizabeth (Irish studies (Syracuse, N.Y.), 1994)
In the midst of an explosion of interest in the field of autobiography, there have developed critical languages and approaches that allow us to read both George Moore's fiction and his fictive autobiographies in new and exciting ways. Elizabeth Grubgeld presents a fresh look at the diverse experiments in fiction and the highly ironic and multi-generic performances Moore put forth as his life story. She focuses on the tension between Moore's fascination with deterministic theories of human behavior and his need to assert a principle of self-creation, his "autogenous self."